Methodological and reporting quality of systematic reviews referenced in the clinical practice guideline for pediatric high-blood pressure. Issue 3 (March 2019) - Vaughn, Kaleb; Skinner, Mason; Vaughn, Victoria; Wayant, Cole; Vassar, Matt
Abstract : Objective: To examine the quality of evidence supporting the Clinical Practice Guideline for Screening and Management of High Blood Pressure in Children and Adolescents. Methods: Methodological and reporting quality of systematic reviews in the Key Action Statements, Consensus Opinions, and in the reference list were assessed using AMSTAR and The PRISMA checklist. Results: For the systematic reviews within the American Academy of Pediatrics' Guideline as a whole ( n  = 27), a mean of 47.8% of AMSTAR items were appropriately addressed, and a mean of 61% of PRISMA were appropriately reported. The means for items adhered to in the systematic reviews cited by Key Action Statements ( n  = 6) were 44.6% for AMSTAR and 67% for PRISMA. The means for items adhered to in the systematic reviews cited by consensus opinion ( n  = 10) were 41.6% for AMSTAR and 54% for PRISMA. Overall, the AMSTAR and PRISMA scores were highly correlated ( r  = 0.77). Conclusion: This study further substantiates the call for more quality evidence-based research in pediatric hypertension. The overall methodological and reporting quality of the systematic reviews were lacking in the American Academy of Pediatrics Guideline. Assessment of risk of bias across studies, identification of an accessible protocol, full disclosure of the role of funding entities, funding of included studies, and a complete PICOS statement were areas of greatest concern. These deficiencies should be addressed in future research in pediatric hypertension.